Biography of literary art. An attempt at a literary project of Tadeusz Kantor - Irena Górska (Przestrzenie Teorii)
In universal consciousness, Tadeusz Kantor is an artist of theatre, painter, creator in other fine arts, but also author of a great number of writings on aesthetics, manifestos, sketches, essays, notes from rehearsals, dramatic scores and of some poems. What is characteristic is that various forms of writing, which by assumption are a theoretical expression of Kantor's ideas on theatre or fine arts, at the same time obtain a character of a literary work while his verses direct one towards theory. Painting, theatre and ideas connected with them are supplemented in the act of writing, which becomes a necessity for Kantor. The author of Dead Class changes the theatrical project into a literary project and in his writing he intermingles drama, commentary, theatre, his own theoretical and biographical reflections, observations of a masterpiece and states of his own consciousness. He plays theatrical ideas not only on the stage but also in theoretical texts and in verses. It is just in writing that the artist from Wielopole establishes anew the relations between theatre, literature and his own biography.